Experimental study on the cemented filled annular tube of ultrafine flotation phosphorus tailings from a phosphorus mine - Li, Shujian; Yang, Jianguang; Wang, Menglai; Pang, Jiantao; You, Jun; Zhu, Yuanting; Pan, Chao; Zhang, Dongming; Yuan, Mingli (Frontiers in Built Environment, 2025)
IntroductionPaste backfilling serves as a key approach for goaf management and mine solid waste disposal. This study investigates the rheological properties of ultra-fine flotation phosphate tailings utilized as backfill aggregates.MethodsTo investigate the pipeline transport characteristics of high-concentration ultra-fine full phosphate tailings under both pumping and gravity flow conditions, this research employed a self-designed industrial-scale paste loop testing system. The pipeline resistance loss of the backfill slurry under various working conditions was systematically measured, and the influence degree of different factors on this resistance was quantified. Furthermore, the rheological parameters of the slurry under different conditions were calculated based on the Bingham fluid model. This allowed for the determination of the slurry's flow regime and critical velocity, and ultimately enabled the back-calculation of the feasible pipeline flow gradient for gravity flow under multiple factor conditions.Results1) Flow velocity had the most significant impact on pipeline resistance loss, followed by flow rate, binder-to-tailings ratio, slurry concentration, and pipe diameter. 2) The flow regime of the backfill slurry was most stable when the flow velocity ranged between 1.4 m/s and 1.8 m/s. 3) Under pumping conditions, the Reynolds number of the backfill slurry was significantly less than 2100, indicating a laminar flow regime within the pipeline. 4) A slurry with a mass concentration of 68% achieved a gravity flow gradient between 7.5 and 9.5 in a pipeline with an internal diameter of 150 mm, confirming the feasibility of gravity flow transport.DiscussionThis study demonstrates that the full phosphate tailings from the Kunyang Phosphate Mine No. 2 are ideal for backfilling due to their favorable gradation. Systematic analysis identified an appropriate pipe diameter range corresponding to economical flow velocities and revealed the weighting of factors affecting pipeline resistance. Flow regime analysis based on the Bingham model confirmed laminar flow within the pipeline, with higher-concentration slurries exhibiting more pronounced structural flow characteristics and a higher critical velocity. Semi-industrial tests finally verified that the 68% concentration slurry can be transported via gravity flow within a pipeline gradient of 10. In conclusion, this research provides crucial theoretical foundation and practical guidance for optimizing pipe diameter, reducing the binder-to-tailings ratio, and controlling flow velocity to achieve economically efficient backfilling while ensuring transport stability.